Anti-tuberculosis activity and structure–activity relationships of oxygenated tricyclic carbazole alkaloids and synthetic derivatives. Issue 22 (15th November 2017) - Börger, Carsten; Brütting, Christian; Julich-Gruner, Konstanze K.; Hesse, Ronny; Kumar, V. Pavan; Kutz, Sebastian K.; Rönnefahrt, Marika; Thomas, Claudia; Wan, Baojie; Franzblau, Scott G.; Knölker, Hans-Joachim
Graphical abstract: Abstract: A series of 49 oxygenated tricyclic carbazole derivatives has been tested for inhibition of the growth of Mycobacterium tuberculosis and a mammalian cell line (vero cells). From this series, twelve carbazoles showed a significant anti-TB activity. The four most active compounds were the naturally occurring carbazole alkaloids clauszoline-M (45 ), murrayaline-C (41 ), carbalexin-C (27 ), and the synthetic carbazole derivative22 with MIC90 values ranging from 1.5 to 3.7 μM. The active compounds were virtually nontoxic for the mammalian cell line in the concentration range up to 50 μM.